2021
DOI: 10.32674/jimphe.v5i1.2643
|View full text |Cite
|
Sign up to set email alerts
|

Are they paying attention, or are they shoe-shopping? Evidence from online learning

Abstract: In response to the coronavirus pandemic, schools across the nation made an abrupt transition to teaching online as states instituted stay-at-home measures. This mixed methods study examines the attentiveness of adult learners in an online Doctorate of Education program. Three main findings emerged: 1) online courses where the students and instructor all are logged on to Zoom synchronously had higher average attentiveness compared to hybrid format courses where some students are physically in the classroom and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…It was seen that the most common situation in children was the inability to concentrate and boredom. Consistent with these findings, in the study conducted by Erbil et al (2021) and Smith et al (2020), it was stated that students have attention problems in distance education.…”
Section: öNerilersupporting
confidence: 59%
“…It was seen that the most common situation in children was the inability to concentrate and boredom. Consistent with these findings, in the study conducted by Erbil et al (2021) and Smith et al (2020), it was stated that students have attention problems in distance education.…”
Section: öNerilersupporting
confidence: 59%
“…The sudden switch to online education during the Corona pandemic was about appropriating platforms that were not designed for education and trying to make them work somehow. This experiment backfired, and this was visible especially in how students lost control over their attention and, instead of fluctuating attention, they experienced hyper attention (Hayles 2007) visible through the constant switching between tabs and applications, scattering their attention while attending online lectures (Smith & Schreder, 2020). While there is a difference between asynchronous and synchronous online education (or between digital and online education), the difference seems to lie more in how active the students are required to be and not so much in the mediation of the screen.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration during the initial planning and implementation of a videoconferencing session is its length of time. Scholars suggest that the optimal duration of a session ranges from 30 to 90 minutes (Alhlak et al, 2012;Correia et al, 2020;Hoyt et al, 2013;Mpungose, 2021;Smith et al, 2020). Engaging in shorter sessions lessens the strain on learners and allows for more concentrated dialogue to evolve.…”
Section: Planning Guidelinesmentioning
confidence: 99%
“…Our exploration of the literature has determined that shorter sessions are more productive than those of a longer duration. Smith et al (2020) reported that students often multitask during long synchronous sessions and that "if the professor used solely lecture as the pedagogical approach, there was very little that could keep the students focused the whole time" (p. 204). Shorter sessions lead to greater engagement and enthusiasm for future learning.…”
Section: Planning Guidelinesmentioning
confidence: 99%